Christians and Muslims in early Islamic Egypt (Durham, NC)
x, 213 sayfa
Keywords: “This volume collects studies exploring the relationship of Christians and Muslims in everyday life in Early Islamic Egypt (642-10th c.) focusing mainly, but not exclusively on administrative and social history. The contributions concentrate on the papyrological documentation preserved in Greek, Coptic, and Arabic. By doing so, this book transcends traditional disciplinary boundaries and offers results based on a holistic view of the documentary material. The articles of this volume discuss various aspects of change and continuity from Byzantine to Islamic Egypt and offer also the (re)edition of 23 papyrus documents in Greek, Coptic, and Arabic. The authors provide a showcase of recent papyrological research on this under-studied, but dynamically evolving field. After an introduction by the editor of the volume that outlines the most important trends and developments of the period, the first two essays shed light on Egypt as part of the Caliphate. The following six articles, the bulk of the volume, deal with the interaction and involvement of the Egyptian population with the new Muslim administrative apparatus. The last three studies of the volume focus on naming practices and language change.” --